PROBIOTIC SUPPLEMENTATION SACCHAROMYCES SPP. (YEAST TAPE) IN rations AGAINST LANDRACE PORK CARCASSE WEIGHT - I G. B., Kesawadana; Wibawa, A.A.P.P.; Puspani, E. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of saccharomyces spp probiotic supplementation (yeast tape) in rations to commercial scraps of landrace pig carcass. This research was conducted in Banjar Kamasan, Dajan Peken Village, Tabanan District, Tabanan Regency and lasted for approximately three months. This study used a completely randomized design (CRD) consisting of 4 treatments, namely P0; Landrace pigs that were given rations without the probiotic Saccharomyces spp. (yeast tape) as control, P1; Cross landrace pigs fed with probiotic Saccharomyces spp. (yeast tape) of 0.1%, P2; Cross landrace pigs fed with probiotic Saccharomyces spp. (yeast tape) of 0.2%; and P3; Cross landrace pigs fed with probiotic Saccharomyces spp. (yeast tape) of 0.3%. Each treatment has 4 replications. The variables observed were commercial carcass chips, namely Ham, Loin, Spare Ribs, Picnic, Boston Butt, and Bacon Bally. The results of this study indicate that the administration od probiotic Saccharomyces spp. (yeast tape) 0,1% in treatment P1, 0,2% ini treatment P2 and 0,3% in treatment P3 in rations can significantly increase the weight of spare ribs, loin, ham, boston butt and picnic. While the fraction of bacon bally has not had a significant effect but the weight of bacon bally has increased. The conclusions obtained from the research that has been done is the administration of probiotics Saccharomyces spp. (yeast tape) 0.1% - 0.3% in real rations can increase the carcass weight of spare ribs, loin, ham, boston butt and picnic, while the weight of bally bacon carcass fragments experienced a non-significant increase.